TOWARDS SUSTAINABLE INTENSIVE DAIRY FARMING IN EUROPE - WACHENDORF, M.; GOLI?SKI, P. (Pastos, 2011)
Increased production from grassland has been achieved at considerable environmental costs, including the loss of biodiversity, many wildlife habitats and landscapes. Since the 1980s policy makers in many European countries require that elements of a sustainable forage production be addressed by researchers. In many European countries intensive dairy farms are facing diffculties in achieving these goals, with nitrogen surpluses and losses being a major topic in large parts of northern continental Europe, where sandy soils predominate. Results from two comprehensive studies (experimental farms Karkendamm and De Marke) show the current nitrogen status of forage-based dairy production in this area and identify shortcomings in the production systems which should be improved in the future. Simulations with the worldwide leading modelling system IFSM (Integrated Farming System Model) verify the long-term effects of technological changes and point at potential solutions for the actual dilemma. Among many agronomical factors determining feed production for dairy cows grassland cultivation and renovation is a quite important issue. A literature review indicates that little knowledge exists in many aspects but also shows that the application of good farming practices can reduce the environmental risks for dairy dominated regions. Keywords: Grassland management, sustainability, nitrogen losses, energy effciency